Risk profile, clinical presentation, and determinants of stroke subtypes among patients with stroke admitted to public referral hospitals, Northwest Ethiopia in 2021: A cross-sectional study - Ayehu, Gashaw Walle; Yitbarek, Getachew Yideg; Zewdie, Edgiet Abebe; Amsalu, Bedemariam Tadesse; Abie, Yonatan; Atlaw, Daniel; Agegnehu, Assefa; Admasu, Fitalew Tadele; Azanaw, Melkalem Mamuye; Amare, Abraham Tsedalu; Emiru, Zemen Asmare (Frontiers in Neurology, 2022)
Background: stroke is the second leading cause of death, burden estimates confirmed a significant increase in stroke burden in the world over the last two and half decades, especially in developing countries. African countries are undergoing an epidemiological transition from infectious disease dominated to double burdened by non-communicable diseases and existing infectious diseases driven by socio-demographic, lifestyle changes, and the ill-health system. Data regarding risk profile, clinical presentation, and predictors of stroke subtype are still limited. Hence, the main aim of this study was to assess the risk profile, clinical presentation, and predictors of stroke in public referral Hospitals, in Northwest Ethiopia. Methods: Five hundred fifty-four stroke patients admitted to three public Referral Hospitals were prospectively followed. Data were collected using a pre-tested interviewer-administered questionnaire. STATA Version 16 was used for data analyses. Candidate variables significant in bivariate analysis were selected for multivariate binary logistic regression and Statistical significance was set at a p-value <0.05. Results: From 554 stroke patients, 60.3% had an ischemic stroke. The mean age of the participants was 61 ± 12.85 years and more than half (53.25%) were females. The most common risk factor identified was hypertension (29.7%) followed by CHF. The most common clinical presentation was hemiparesis complained by (57.7%) of patients followed by loss of consciousness (20.7%) and aphasia (9%). After multivariable logistic regression; age (AOR=1.03, 95% CI:1.01-1.05) sedentary physical activity level (AOR=6.78, 95% CI:1.97-23.32), absence of a family history of chronic illness (AOR = 3.79, 95% CI:2.21-6.48), hypertension (AOR=0.51, 95% CI:0.31-0.85) and past stroke (AOR=3.54, 95% CI:0.93-13.49) were independent determinants of stroke subtype. Conclusion: Age, sedentary physical activity level, absence of a family history of chronic illness, hypertension, and past stroke, were independent determinants of stroke subtype.